The Impact of Gasfier Stoves Use on Socio-Economic and Environment in Tanzania: The Case of Arusha and Moshi Municipalities - Mwakaje, Agnes Godfrey (Journal of Technology Innovations in Renewable Energy, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> This study examined the socio-economic and environmental impact of the adoption of gasfier stoves by households in Arusha and Moshi towns in Tanzania. A total of 55 respondents were selected purposely from the gasfier stoves. For comparative purposes another 55 charcoal users were selected randomly for interview making a total sample of 110. There were also focus group consultations and key informant interviews. Structured and semi-structured questionnaires were used to collect data, which were analysed using the Statistical Package for Social Sciences. The results show that the respondents who were using gasfier stoves had significant reduction (p=0.001) in the cost of energy for cooking compared to charcoal stove users by spending only T.shs 13,396 per month compared to T.shs 36,932 for charcoal users. The use of gasfier stoves also had a positive impact on the environment. Findings show that by using gasfier stoves 15.4 ha were saved from deforestation per annum and about 365.4.tonnes of carbon were saved for sequestration an act that reduces carbon emissions and global warming. Nevertheless, despite the impressive performance of gasfier stoves for cooking, the rate of adoption has remained low. The main reason for this was reported to be the high price, poor quality of the pellets and unfriendly usability. The adoption of gasfier stoves could only be enhanced by addressing these constraining factors. <!–[endif] –>